Efeitos de bivalves, gastrópodes e fatores ambientais sobre a abundância de macroinvertebrados em lagoas adjacentes ao Rio Cuiabá-MT - Beliene, Glieber Henriques (2015)
Interactions between organisms of one community can determine the distribution and abundance of species. The results of these interactions can be positive or negative. In addition to the interactions, there are several environmental factors influencing these relationships. In aquatic environments, molluscs induce changes in the macrobenthic community, changing the distribution and abundance of these organisms. Because of this, investigated the effects of bivalves, exotic gastropod Melanoides tuberculatus and environmental variables on the abundance of the benthic macroinvertebrate community in lakes near the river Cuiabá. The abundance of macroinvertebrates seem to be affected by environmental variables. it also varied according to presence and absence of Bivalve and M. tuberculatus. Noticed that Ceratopogonidae, Hirudinea and Ostracoda negatively answered variables (Hardness and Turbidity); Chironomidae, Ceratopogonidae, Oligochaeta negatively answered the presence of M. tuberculatus; Zygoptera, Ostracoda and Oligochaeta responded positively to the presence of Bivalve. Other variables that were not measured here can influence the interactions discussed here, making a topic for future work.